1985
DOI: 10.1177/000992288502400707
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for ABO Hemolytic Disease

Abstract: Confusion still exists regarding the true incidence of ABO hemolytic disease and the significance of the various laboratory investigations commonly employed in its evaluation. With such imprecision in diagnosis, early hospital discharge of newborns can be a potential problem. To evaluate the usefulness of more extensive screening than commonly employed and to identify possible indicators of severity, a pilot study of cord blood screening was undertaken. In the study, 1391 cord blood specimens were tested for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
0
12
1
1
Order By: Relevance
“…37 Levine and Meyer opined that confusion existed regarding the true incidence of ABO-HDFN, because of the ambiguity in the significance of various laboratory investigations commonly employed for its evaluation. 38 This could be the reason for disparity of results in previous studies and our study.…”
Section: Discussioncontrasting
confidence: 74%
“…37 Levine and Meyer opined that confusion existed regarding the true incidence of ABO-HDFN, because of the ambiguity in the significance of various laboratory investigations commonly employed for its evaluation. 38 This could be the reason for disparity of results in previous studies and our study.…”
Section: Discussioncontrasting
confidence: 74%
“…1 Diagnostic applicability of DAT in ABO HDFN has a wide range of controversies. According to Levine et al and Schonitzer et al DAT was neither a tool for diagnosis nor a predictor of severity of disease, while it was found to be beneficial for establishing ABO HDFN by Bel et al, Dufour et al and Whyte et al 24,25,5,26,27 Dinesh had postulated that in infants with clinically significant haemolysis, 80% had a positive DAT. 28 While Bjarte and Morten opined that antepartum and postpartum serologic tests were poor predictors of ABO haemolytic disease, Umit et al suggested that reticulocyte count, a positive DAT and the presence of a sibling with neonatal jaundice were good predictors for the development of significant hyperbilirubinaemia and severe haemolytic disease.…”
Section: Discussionmentioning
confidence: 99%
“…26 David et al and Quinn et al observed that DAT was neither diagnostic nor predictive of severity in ABO HDFN. 27,20 Density of A and B antigens in cord red cells was studied using an immuno-enzymatic assay and no statistically significant association was found between antigen maturity and severity of ABO HDFN.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical course and severity of subsequent hyperbilirubinaemia or isommune disease is diffi cult to predict in a newborn with ABO incompa bility because there is no single test that is of high predic ve value 15,16 .…”
Section: Discussionmentioning
confidence: 99%